The Effect of Coffee Pulp Fermentation in Ransum to IOFC and Feed Convertion Etawa Crossbreed Goat (PE) - basofi rohmat (Jurnal Sains Peternakan, 2015)
ABSTRACT This research aims to determine the effect of fermented coffee peel waste within complete feed toward income over feed cost and the goat peranakan etawa (PE) feed conversion. Subject used in this research was 9 goats male Peranakan etawa (PE) with an average  weight  of  22-29  kg.  The  experimental  method  in  this  research  consists  of  3 treatments with 3 replications livestock. Control treatment P0 pollard 100%; P1 pollard 50%+ KKF 50%; P2 pollard 40% + KKF 60%. The variables measured in this research is income over feed cost and feed conversion. The result of this research is the addition of feed KKF in pollard feed gave the significant effects to the income over feed cost and feed conversion (P<0,05). The average income over feed cost is P0, P1, P2, respectively 106 233; 162 195; 75 963 an the respectively of feed conversion is P0, P1, P2 respectively 7.09; 6.37; 11.25. So, the researcher conclude that the significance of using fermented waste leather coffee in ransum could increase the value of IOFC and made the feed conversion became good, with adding 50% of KKF feed to the goat peranakan etawa (PE) Pollard feed. Keywords: Feed goats, experimental research, income over feed Cost, feed conversion